COMMUNITY PARTICIPATION FISHERMAN IN DEVELOPING A MARINE TOURISM DESTINATION IN MURSALA ISLAND IN KALANGAN VILLAGE KABUPATEN TAPANULI TENGAH POVINSI SUMATERA UTARA - Irhamsyah Hasibuan; Zulkarnain Zulkarnain; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in July 2018 in the Kalangan District of Central Tapanuli Regency, North Sumatra Province, on Community Participation in developing marine tourism in Mursala Island. This study aims to find out how the form and level of community participation in the marine tourism destination of Mursala Island. The method used is the survey method with the number of respondents as many as 25 people from 100 populations and distributed questionnaires to respondents.The results of the study show that most of the people in the village have a livelihood as fishermen and have a side livelihood as a tour guide on the island of Mursala. The form of community participation in the development of marine tourism involves directly those who provide lodging, tour guides and security guards. Indirect participation, namely tourists, cleaning guards, cooperative management and fishing households. The level of community participation in the development of marine tourism in Mursala Island is divided into 4 categories, namely, planning based on the data that is known that the community interviewed with the participation rate is still at a moderate level amounting to 44%. Management is based on known data that the community with a low level of participation is 48%. Decision making is based on data that is known that the community interviewed with a low level of participation is 64%. The level of control participation is based on the data that is known that the people interviewed with a low level of participation are 56%. From the results of research carried out in the village circles about community participation in the development of the island of Mursala is still said to be at a low stage, starting from the utilization of the maritime area, providing lodging, tour guides, providing transportation and so on. Keywords: Community Participation, Community Based Tourism, Mursala Island